Dynamic role of LMW-hyaluronan fragments and Toll-like receptors 2,4 in progression of bleomycin induced lung parenchymal injury to fibrosis - Pandey, Apoorva; Kulshrestha, Ritu; Bansal, Surendra Kumar (Egyptian Journal of Bronchology, 2021)
Background Pulmonary fibrosis (PF) is a progressive and lethal lung disease of elderly whose incidence has been increasing following the Covid-19 pandemic caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). PF immunopathogenesis involves progressive alveolar epithelial cell damage, release of damage-associated molecular patterns (DAMPs), and extracellular matrix (ECM) injury. We assessed the dynamic role of LMW-hyaluronan (LMW-HA) as DAMP in initiation of host immune TLR-2,4 responses and as determinant in progression of ECM injury to fibrosis. Male Wistar rats were divided into Group I (saline control, n = 24) and Group II (intratracheal bleomycin, 7 U/kg/animal, n = 24). Animals were euthanized on 0, 7, 14, and 28 days. The time course of release of LMW-HA, TLR-2,4 mRNA and protein levels, and NF-κB-p65 levels after bleomycin injury were correlated with the development of parenchymal inflammation, remodelling, and fibrosis. Results Acute lung injury caused by bleomycin significantly increases the pro-inflammatory LMW-HA levels and elevates TLR-2,4 levels on day 7. Subsequently, TLR-2 upregulation, TLR-4 downregulation, and NF-κB signalling follow on days 14 and 28. This results in progressive tissue inflammation, alveolar and interstitial macrophage accumulation, and fibrosis. Conclusions LMW-HA significantly increases in PF caused by non-infectious and infectious (Covid-19) etiologies. The accumulating HA fragments function as endogenous DAMPs and trigger inflammatory responses, through differential TLR2 and TLR4 signalling, thus promoting inflammation and macrophage influx. LMW-HA are reflective of the state of ongoing tissue inflammation and may be considered as a natural biosensor for fibrotic lung diseases and as potential therapeutic targets.